2016
DOI: 10.1161/circresaha.116.308544
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Adult Cardiac Myocyte GSK-3 Leads to Mitotic Catastrophe Resulting in Fatal Dilated Cardiomyopathy

Abstract: Rationale Cardiac myocyte-specific deletion of either Glycogen Synthase Kinase (GSK)3A or GSK3B leads to cardiac protection following myocardial infarction, suggesting that deletion of both isoforms may provide synergistic protection. This is an important consideration due to the fact that all GSK-3–targeted drugs including the drugs already in clinical trial target both isoforms of GSK-3 and none are isoform specific. Objective To identify the consequences of combined deletion of cardiac myocyte GSK3A and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 66 publications
7
69
0
Order By: Relevance
“…Interestingly, a significant increase in smaller mono-nucleated CMs was seen in miR-210 group, while the number of multi-nucleated CMs was reduced. This observation supports CM cell cycle re-entry resulting in proliferation, and reduced mitotic catastrophe-induced cell death as reported by earlier studies [36]. In continuation, we observed fourfold increment in EdU and Ki67 labeling in miR-210 transfected CMs as compared to control, while the cell number was almost double in miR-210 group.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, a significant increase in smaller mono-nucleated CMs was seen in miR-210 group, while the number of multi-nucleated CMs was reduced. This observation supports CM cell cycle re-entry resulting in proliferation, and reduced mitotic catastrophe-induced cell death as reported by earlier studies [36]. In continuation, we observed fourfold increment in EdU and Ki67 labeling in miR-210 transfected CMs as compared to control, while the cell number was almost double in miR-210 group.…”
Section: Discussionsupporting
confidence: 92%
“…Karlstaedt and Taegtmeyer for their favorable comments on our recent report demonstrating mitotic catastrophe as a key mechanism of fatal dilated cardiomyopathy in GSK-3 deficient hearts (conditional GSK-3α/β double knockout, DKO). 1 Considering the complex biology of GSK-3 in regulating numerous biological processes and cellular functions, we completely agree with Drs. Karlstaedt and Taegtmeyer that there may be additional layer(s) of complexity to be elucidated for the complete understanding of the molecular basis of the observed phenotype.…”
supporting
confidence: 69%
“…Using neonatal rat cardiac fibroblasts, we further investigated the antifibrotic signaling of SDT and its interaction with the fibrotic signaling of TGF-β1. Many studies have indicated that GSK3β regulates the activities of several metabolic, signaling and structural proteins [25][26][27], and play an important role in CF activation and fibrotic remodeling after myocardial infarction [24]. Forde et al reported that GSK3β deletion leads to hyperactivation of profibrotic TGF-β1/SMAD3 signaling that is associated with excessive fibrosis and adverse ventricular remodeling [28].…”
Section: Discussionmentioning
confidence: 99%